(untitled) (Revista de Artes Marciales Asiáticas, 2019)
This study consists of a description on pre-reflexive processes in learning how to fight. The objective of this investigation is to present and discuss them through phenomenology as a philosophical and methodological point of view. It is a way to comprehend each phenomenon from its own structure, not apart from the reality of those who live it. In embodied corporal practices, the body constantly moves and there is not much time for the practitioner to reflect before choosing and doing each technique. We briefly present the main concepts to promote an understanding on pre-reflexive acts through phenomenology: body, awareness/consciousness, perception, body schema, habit. This can broaden the way we usually see the learning processes, which cannot count only on explanation of techniques. A practice to be embodied must be lived by the body. We must enable the bodies to be challenged not only to learn or master a technique but also to generate new perceptions and movements in the situations we are in. One can only learn how to fight when fighting.